Assessment Of The Influence Of Changes In The Hydrological Regime On The Forest Plant Community (Texas Journal of Agriculture and Biological Sciences, 2025)
The article assesses the impact of changes in the hydrological regime on the tugai plant community. According to the research results, it was established that the dynamics of groundwater influences tugai vegetation. As a result of changes in the hydrological regime in the lower reaches of the Amu Darya, the process of halophytosis of soil and vegetation significantly intensified, which began with the regulation of river flow, which led to the emergence of various halophytic variants of tugai forests and the degradation of typical tugai ecosystems.